Morphology and Postdepositional Dynamics of Eggs of the Predator Podisus distinctus (Stål) (Heteroptera: Pentatomidae: Asopinae) - de Sá, Veríssimo Gibran Mendes; Zanuncio, José Cola; Soares, Marcus Alvarenga; Rosa, Cassiano Sousa; Serrão, José Eduardo (Zootaxa, 2013)
The predator Podisus distinctus (Stål) (Heteroptera: Pentatomidae: Asopinae) has been reared to control lepidopteran de-foliators. In this study, we describe this predator’s morphology, postdepositional dynamics and eggs in different develop-mental stages under scanning electron microscope. Its eggs are subglobular and ovoid, narrower at the base than at the top, with a convex, circular operculum. They measure 1.09±0.03 mm in height and 0.90±0.04 mm in diameter. The aero-mi-cropylar processes number 16.00±2.00 and are arranged radially at the egg anterior pole. Immediately after laying, the egg color is pearl-like, and soon after turns gray. Orientation of the spine-like projections and aero-micropylar processes also change after deposition. Though the eggs of P. distinctus are similar to those of other species of the genus Podisus, certain aspects, including the egg size and shape, chorion micro-sculptures, and number of aero-micropylar processes, are specif-ic, allowing for differentiation from other related species.